Schwarz on tax treaties - Schwarz, Jonathan (Kluwer Law International B. V., 2021)
Schwarz on Tax Treaties', now in its sixth edition, is the definitive analysis of tax treaties from United Kingdom and Irish perspectives and provides in-depth expert analysis of the interpretation and interaction of those treaty networks with not only the European Union and international law but also their own tax rules, administrative law and constitutional rules whose variations reflect domestic values of each society. Thus, treaties need to be seen both in their international context and the wider legal systems of contracting states.00This edition significantly develops the earlier work with enhanced commentary and is updated to include the latest UK and Irish domestic law and treaty developments, international and EU law.